Skulptur im 20.Jahrhundert. - Merian-Park, Basel (Basel : Merian-Park, 1984)
Andre, Carl ; Anselmo, Giovanni ; Archipenko, Alexander ; Arman ; Arp, Jean ; Balla, Giacomo ; Barlach, Ernst ; Baselitz, Georg ; Belling, Rudolf ; Bellmer, Hans ; Béothy, Etienne ; Beuys, Joseph ; Boccioni, Umberto ; Bodmer, Walter ; Brancusi, Constantin ; Broodthaers, Marcel ; Byars, James Lee ; etc.
bijlage: persdossier
Skulptur im 20.Jahrhundert, Merian-Park, Basel, 3. Juni - 30. September 1984
boek